Regular Aerobic, Resistance, and Cross-Training Exercise Prevents Reduced Vascular Function Following a High Sugar or High Fat Mixed Meal in Young Healthy Adults - Das, Emon K.; Lai, Pui Y.; Robinson, Austin T.; Pleuss, Joan; Ali, Mohamed M.; Haus, Jacob M.; Gutterman, David D.; Phillips, Shane A. (Frontiers in Physiology, 2018)
The postprandial state can negatively influence flow mediated dilation (FMD), a predictor of atherosclerosis and cardiovascular disease. This investigation was designed to determine the effect of regular aerobic and/or resistance exercise on postprandial FMD after a high sugar or high fat mixed meal. Forty-five healthy participants were recruited from one of four groups: lean sedentary (SED), runners, weight lifters, and cross-trainers. Participants were randomly crossed over to a high sugar meal (HSM) and a high fat mixed meal (HFMM; both fat and carbohydrate). Pre-and postprandial endothelial function was assessed after both meals using brachial artery FMD. Plasma lipids, insulin, glucose, hs-CRP, and SOD were also measured following each meal. Endothelium-independent dilation was determined via sublingual nitroglycerin. Brachial artery FMD was reduced in SED following the HSM (9.9±0.9% at baseline, peak reduction at 60 min 6.5±1.0%) and the HFMM (9.4±0.9% at baseline, peak reduction at 120 min 5.9±1.2%; P < 0.05 for both, Mean±SEM). There was no change in FMD after either HSM or HFMM in runners, weight lifters, and cross-trainers. Post-prandial increases in blood glucose, insulin and triglycerides were less pronounced in the exercisers compared to SED. In addition, exercisers presented lower baseline plasma hs-CRP and higher SOD activity. Nitroglycerin responses were similar among groups. These results suggest that endothelial function is reduced in sedentary adults after a HSM or HFMM, but not in regular aerobic or resistance exercisers. This response may be due to favorable postprandial metabolic responses or lower postprandial levels of inflammation and oxidative stress. These findings may help to explain the cardioprotective effect of exercise.